Open data and access to public information in the reconstruction of digital history - Magallón, Raúl (Historia y Comunicación Social, 2017)
The aim of this article is to describe and rethink on the role of access to public information and open data in the reconstruction of historical, collective and social memory. The appearance of new formats not only modifies the role of the historian but it also transforms form and content of the story.The issue of open data and access to public information should be analyzed from two perspectives: from those events of the past that are updated after the disclosure of new documentation that expands the perspective of what happened and from the present with those media events that from the moment they occur, they mark the development of future history.
Keywords: digital history; narration; open data; digital humanities.